Pengaruh Intellectual Capital dan Intensitas Research and Development (R&D) terhadap Nilai Perusahaan - Aziz, Nurul Fatimah; Arza, Fefri Indra (Jurnal Eksplorasi Akuntansi, 2025)
“The primary issue in this research is how intellectual capital and the intensity of research and development (R&D) affect the corporate value in the F&B sector listed on the Indonesia Stock Exchange (IDX) from 2018 until 2022. The impact of R&D intensity and intellectual capital on corporate value serves as an important indicator of a firm’s growth prospects. This study employs a quantitative approach with hypothesis testing, utilizing secondary data. The findings reveal that human resources has a positive impact on corporate value”, whereas R&D intensity negatively influences the firm's worth.